Використання методів ситуаційного аналізу в управлінні проектами з врахуванням сезонності виробництва - Прокопенко, Т. О.; Коломицева, О. В. (НТУ "ХПІ", 2016)
Пропонується застосування методів нечіткого ситуаційного підходу, що забезпечують прийняття рішень в управлінні проектами на підприємствах з сезонним характером виробництва. Представлена модель нечіткого ситуаційного графа управління проектом на інвестиційній фазі. Зроблено висновки про можливість вибору альтернативних стратегічних рішень для підприємств з врахуванням сезонності виробництва на основі запропонованого нечіткого ситуаційного графа рішень.

There have been proposed methods of fuzzy situational approach, providing decision-making in project management in enterprises with seasonal nature of production. The model of fuzzy graph situational project management in the investment phase, providing adequate and effective opportunity to describe the project taking into account seasonality and uncertainty in the tasks of planning and decision making. The conclusions about the choice of alternative strategic solutions for companies considering the seasonality of production based on the proposed fuzzy graph situational solutions that allow for the special factors such as the nature of the project and the environment; uncertainty in the design and environment; take account of the conditions of the process; and evaluate the results of actions and make choices alternatives for achieving the strategic objectives of the various activities of the enterprise, taking into account the seasonal factor.
Using the method of situational analysis in project management taking into account seasonality of production
Keywords: нечіткий ситуаційний підхід; прийняття стратегічних рішень; невизначеність; стратегічні показники; seasonality of production; fuzzy situational approach; project management; strategic decision making